2016
DOI: 10.1111/dth.12398
|View full text |Cite
|
Sign up to set email alerts
|

Oral sildenafil as a treatment option for lymphatic malformations in PIK3CA-related tissue overgrowth syndromes

Abstract: Patients with extensive lymphatic malformations associated with tissue overgrowth syndromes (such as Klippel-Trenaunay syndrome and CLOVES) often pose a therapeutic challenge for physicians. In recent years, it has been suggested that oral sildenafil therapy might be used to treat congenital lymphatic malformations. However, this possible new therapy has not yet been used in patients with lymphatic malformations associated with tissue overgrowth syndromes. A 30-year-old man with extensive capillary-lymphatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…With the identification of PIK3CA mutations in LMs (14), there has been increased use of sirolimus therapy (15)(16)(17)(18), because mTOR inhibition reduces downstream signaling of PI3 kinase, inhibiting cell proliferation. A case report has also documented improvement of LM symptoms with sildenafil treatment in an individual with PIK3CA-related overgrowth syndrome (19).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…With the identification of PIK3CA mutations in LMs (14), there has been increased use of sirolimus therapy (15)(16)(17)(18), because mTOR inhibition reduces downstream signaling of PI3 kinase, inhibiting cell proliferation. A case report has also documented improvement of LM symptoms with sildenafil treatment in an individual with PIK3CA-related overgrowth syndrome (19).…”
Section: Discussionmentioning
confidence: 95%
“…Sildenafil's hypothesized effects on LMs are that the resulting smooth muscle relaxation perpetuates cystic decompression and allows secondary lymphatic spaces to open or that sildenafil mobilizes normal lymphatic progenitor cells to reduce lymphatic endothelial dysfunction at disease sites . These mechanisms may collectively account for the reported softening and improvement in LM symptoms . Mouse models and human studies have identified increased circulating endothelial and hematopoietic progenitor cells with PDE‐5 inhibition , suggesting an alternative mechanism of action for sildenafil.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus has a role in the treatment of both PIK3CArelated overgrowth and non-PROS growth disorders but it is clear that such medical therapies are still in their infancy (Adams et al 2016;Horbach et al 2016). More specific gene mutations need to be identified so that the vast range of differing phenotypes can be targeted more effectively.…”
Section: Mixed Lesions and Overgrowth Syndromesmentioning
confidence: 99%
“…In addition, some other beta-blockers (atenolol [11], timolol [12], etc. ), itraconazole [13], rapamycin (sirolimus) [14] and sildenafil [15,16] have been reported to be effective in treating certain vascular anomalies.…”
Section: Introductionmentioning
confidence: 99%